Islamisme, Melayu Muslim, dan Revivalisme Islam di Asia Tenggara - Karim, Syahrir (UIN ALAUDDIN MAKASSAR, 2024)
In this article, will discuss Islam and Malays and their relationship with the current of Islamic revivalism. Next, will discuss the discourse on Malay Islamic identity, which is often a topic of discussion among intellectuals, especially Malay Muslims. In the past, it could be said that Islamic civilization was visible in the Middle East and Europe, so in the current era of globalization, many believe that the Islamic revival will emerge from Southeast Asia. Indonesia and Malaysia are the most important parts that have the potential to lead the new Islamic world. In this modern century, there is no longer any optimism that the Middle East, let alone Europe, will be able to maintain the glory of civilization that has been etched on the stage of history. The phenomenon of Islamism will increasingly emphasize the identity of the Islamic community as a political, economic, and even technological force in Southeast Asia. Islamic movements in the form of Islamic revivalism are seen as increasingly showing a much more multireligious, multicultural, moderate, and pluralistic color of Islam that which carries democratic values.